Analisis Strategi Pengembangan Pariwisata Halal Dalam Meningkatkan Pendapatan Asli Daerah (PAD) Kabupaten Bener Meriah di Masa New Normal - Nasution, Fachrul Rozzi; ,M.Si, Yusrizal; Harahap, Muhammad Ikhsan (Universitas Muhammadiyah Sumatera Utara, 2022)
Halal tourism is considered a new way to develop tourism that upholds Islamic culture and values. This study aims to see how the strategy of the Bener Meriah Regency Tourism Office in developing halal tourism in the new normal period. This research is qualitative, while the data analysis technique used is descriptive with SWOT analysis. The results of the study show that the strategy carried out by the Tourism Office of Bener Meriah Regency in developing its tourism in the New Normal period is empowering communities whose villages have tourism potential through training and tourism awareness counseling, training and counseling on the application of health protocols at tourist attractions and developing halal tourism from social capital, natural capital, and cultural capital. The location of the SWOT analysis is at the quadrant I level, including the Growth Orianted Strategy, which uses strengths in the development of halal tourism to seek and take full advantage of opportunities in developing halal tourism which can increase PAD in Bener Meriah Regency.